Biochar carbon dynamics in physically separated fractions and microbial use efficiency in contrasting soils under temperate pastures. (January 2018) - Fang, Yunying; Singh, Bhupinder Pal; Luo, Yu; Boersma, Mark; Van Zwieten, Lukas
Abstract: There is overwhelming evidence for the long-term persistence of biochar in soil. However, the partitioning of biochar into light and heavy carbon (C) fractions and microbial biomass C (MBC), and the dynamics of C use efficiency (CUEE : net incorporation of biochar into MBC per unit of biochar-C consumed, including microbial death and recycling of biochar-derived microbial metabolites) in planted soil systems are poorly understood. A 13 C-labelled wood biochar (δ 13 C: −36.7‰) was incorporated into topsoil (0–10 cm) in an Arenosol, Cambisol and Ferralsol under C3 dominated temperate pastures (δ 13 C: −25 to −27‰). The partitioning of biochar-C into the various soil C pools and CUEE were measured at 4, 8 and 12 months. The results showed that 8.6–28.2% of the biochar-C in the top soils was distributed to the heavy fraction (HF) within 4 months, which increased to 11.0–33.3% at 8 and 12 months. Biochar-C recovery in the HF was the highest in the Ferralsol ( cf. Arenosol and Cambisol), possibly due to greater interaction of biochar and biochar-derived microbial metabolites with soil minerals. Biochar significantly increased MBC across the three soils. Biochar-derived MBC ranged from 22 to 93 mg C kg −1 soil over time (Arenosol < Cambisol < Ferralsol), representing 11–20% of the total MBC pool. Biochar CUEE was 0.20–0.27 at 4 months, which decreased over time, possibly due to lowering of biochar-C availability to microbes. Further, although biochar-derived MBC was higher, biochar CUEE was lower in the Ferralsol ( cf. Arenosol and Cambisol), likely supported by higher microbial respiration and turnover, and lower recycling of microbial metabolites via greater organo-mineral interaction. Here, the study advanced our understanding of key C cycling processes, such as CUEE and the temporal fate of biochar-derived C in an organo-mineral fraction with relevance for biochar sequestration in contrasting soils under planted field conditions. Highlights: Examined biochar's fate in light−heavy C fractions & C use efficiency in soils. Considerable biochar-C was recovered in the heavy fraction (HF) within 4 months. Biochar-C recovery in HF was the highest in Ferralsol ( cf. Arenosol & Cambisol). Biochar-derived MBC was the highest in Ferralsol ( cf. Arenosol & Cambisol). Microbial biochar-C use efficiency was lower in Ferralsol than Arenosol & Cambisol.